Tempering medium-low transmittance three-silver low-emissivity coated glass and preparation method thereof
By plating a multi-layer film structure on the glass, combining silicon nitride, nickel chromium nitride and other materials, the problem of degradation of the shading performance of existing low-radiation glass when increasing the light transmittance is solved, and the optimization of medium and low-transmissive three-silver low-radiation coating glass between light transmittance and sunshade effect is achieved.
Patent Information
- Application Number
- CN202510061596.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-25
AI Technical Summary
While the existing low-radiation glasses increase the light transmittance, their shading performance may be reduced, making it difficult to have a good shading effect while maintaining a certain light transmittance.
A tempered medium-low-transmissive, low-radiation coating glass is used, and its coating layer consists of eighteen film layers, including silicon nitride, nickel chromium nitride, zinc aluminum oxide, silver, nickel chromium alloy, zinc tin oxide and other materials. It is prepared by magnetron sputtering technology, and the total film layer thickness is controlled to be 160-349nm.
It achieves a good sunshade effect while maintaining a certain transmittance. After tempering, the transmittance and color parameters of the glass meet the requirements, and are not prone to scratches or oxidation during long-term transportation and storage.
Smart Images

Figure CN119874213A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of glass deep processing, and specifically relates to a tempered medium-low-transmittance triple-silver low-radiation coated glass and a preparation method thereof. Background Art
[0002] In the field of modern architecture, glass has become an indispensable component due to its beauty, light transmission and structural properties. As society's requirements for architectural aesthetics and functionality continue to increase, glass is no longer just a transparent partition of the structure, but has gradually become an intelligent material that meets multiple functional requirements.
[0003] Low-emissivity glass can effectively reflect indoor heat and reduce heat loss by coating one or more layers of metal or metal oxide film on the glass surface, while allowing natural light to enter and improving lighting effect. However, there is often a trade-off between the performance of this type of glass and its light transmittance and sunshade performance. As the light transmittance increases, although the lighting effect is improved, the sunshade performance may decrease. Therefore, it is necessary to optimize the film layer structure of multi-coated glass so that it can maintain a certain light transmittance while also having good sunshade performance, thereby achieving green energy saving of buildings and improving the comfort of residents. Summary of the invention
[0004] The purpose of the present invention is to provide a tempered medium-low transmittance triple-silver low-emissivity coated glass and a preparation method thereof in order to provide the glass with a certain transmittance and good sunshade effect.
[0005] The object of the present invention can be achieved by the following technical scheme: a tempered medium-low transmittance three-silver low-emissivity coated glass, characterized in that the coated glass comprises a glass substrate layer and a coating layer, and the coating layer is compounded with eighteen film layers in sequence from the glass substrate layer to the outside, wherein the first layer is a silicon nitride layer, the second layer is a nickel-chromium nitride layer, the third layer is a silicon nitride layer, the fourth layer is a zinc-aluminum oxide layer, the fifth layer is a silver layer, the sixth layer is a nickel-chromium alloy layer, the seventh layer is a zinc-aluminum oxide layer, the eighth layer is a zinc-tin oxide layer, the ninth layer is a zinc-aluminum oxide layer, the tenth layer is a silver layer, the eleventh layer is a nickel-chromium alloy layer, the twelfth layer is a zinc-tin oxide layer, the thirteenth layer is a zinc-aluminum oxide layer, the fourteenth layer is a silver layer, the fifteenth layer is a titanium layer, the sixteenth layer is a zinc-aluminum oxide layer, the seventeenth layer is a silicon nitride layer, and the eighteenth layer is a zirconium oxide layer.
[0006] Preferably, the coating thickness of the first layer is 10-40 nanometers, the coating thickness of the second layer is 2-10 nanometers, the coating thickness of the third layer is 5-10 nanometers, the coating thickness of the fourth layer is 5-10 nanometers, the coating thickness of the fifth layer is 10-15 nanometers; the coating thickness of the sixth layer is 1-3 nanometers; the coating thickness of the seventh layer is 10-15 nanometers; the coating thickness of the eighth layer is 15-30 nanometers; the coating thickness of the ninth layer is 10-20 nanometers; The coating thickness of the tenth layer is 10 to 20 nanometers; the coating thickness of the eleventh layer is 1 to 3 nanometers; the coating thickness of the twelfth layer is 30 to 80 nanometers; the coating thickness of the thirteenth layer is 5 to 20 nanometers; the coating thickness of the fourteenth layer is 10 to 20 nanometers; the coating thickness of the fifteenth layer is 1 to 3 nanometers; the coating thickness of the sixteenth layer is 5 to 10 nanometers; the coating thickness of the seventeenth layer is 15 to 30 nanometers; and the coating thickness of the eighteenth layer is 5 to 10 nanometers.
[0007] The method for preparing the above-mentioned tempered medium-low transmittance triple-silver low-emissivity coated glass is characterized in that the method comprises the following steps:
[0008] 1) Select float glass as the glass substrate layer;
[0009] 2) Use a coating-specific washing machine to clean and dry the glass substrate layer. Before coating, the surface of the glass substrate layer must be dry, free of impurities and static electricity; use deionized water for cleaning, and the water resistance must be greater than 10μs / cm;
[0010] 3) Magnetron sputtering coating
[0011] A. Magnetron sputtering first layer
[0012] Target quantity: 1 to 2 AC rotating targets; target configuration is silicon aluminum (SiAl); process gas ratio: argon and nitrogen, the ratio of argon and nitrogen is 7:6; sputtering pressure is 3 to 5×10 -3 mbar;
[0013] B. Magnetron sputtering second layer
[0014] Target quantity: 1 AC rotating target; target configuration is nickel-chromium alloy (NiCr); process gas ratio: argon and nitrogen, argon and oxygen ratio is 6:1; sputtering gas pressure is 3~5×10 -3 mbar;
[0015] C. Magnetron sputtering third layer
[0016] Target quantity: 1 to 2 AC rotating targets; target configuration is silicon aluminum (SiAl); process gas ratio: argon and nitrogen, argon and oxygen ratio is 7:6; sputtering pressure is 3 to 5×10 -3 mbar;
[0017] D. Magnetron sputtering fourth layer
[0018] Target quantity: 2 to 4 DC planar targets; target configuration is zinc-aluminum alloy (ZnAl); process gas ratio: argon and oxygen; sputtering gas pressure is 2 to 3×10 -3 mbar;
[0019] E. Magnetron sputtering fifth layer
[0020] Target quantity: 1 DC plane target; target configuration is silver (Ag); process gas ratio: pure argon; sputtering gas pressure is 2-3×10 -3 mbar;
[0021] F. Magnetron sputtering sixth layer
[0022] Target quantity: 1 AC rotating target; target configuration is nickel-chromium alloy (NiCr); process gas ratio: pure argon; sputtering gas pressure is 2-3×10 -3 mbar;
[0023] G. Magnetron sputtering seventh layer
[0024] Target quantity: 1 to 2 AC rotating targets; target configuration is zinc-aluminum alloy (ZnAl); process gas ratio: argon and oxygen, the ratio of argon and oxygen is 5:9; sputtering gas pressure is 3 to 5×10 -3 mbar;
[0025] H. Magnetron sputtering eighth layer
[0026] Target quantity: 2 to 4 AC rotating targets; target configuration is zinc-tin alloy (ZnSn); process gas ratio: argon and oxygen, the ratio of argon and oxygen is 5:9; sputtering gas pressure is 3 to 5×10 -3 mbar;
[0027] I. Magnetron sputtering ninth layer
[0028] Target quantity: 1 to 2 AC rotating targets; target configuration is zinc-aluminum alloy (ZnAl); process gas ratio: argon and oxygen, the ratio of argon and oxygen is 5:9; sputtering gas pressure is 3 to 5×10-3mbar;
[0029] J. Magnetron sputtering tenth layer
[0030] Target quantity: 1 DC plane target; target configuration is silver (Ag); process gas ratio: pure argon; sputtering gas pressure is 2-3×10 -3 mbar;
[0031] K. Magnetron sputtering eleventh layer
[0032] Target quantity: 1 AC rotating target; target configuration is nickel-chromium alloy (NiCr); process gas ratio: pure argon; sputtering gas pressure is 2-3×10 -3 mbar;
[0033] L. Magnetron sputtering twelfth layer
[0034] Target quantity: 2 to 5 AC rotating targets; target configuration is zinc-tin alloy (ZnSn); process gas ratio: argon and oxygen, the ratio of argon and oxygen is 5:9; sputtering pressure is 3 to 5×10 -3 mbar;
[0035] M, magnetron sputtering thirteenth layer
[0036] Target quantity: 2 to 4 AC plane targets; target configuration is zinc-aluminum alloy (ZnAl); process gas ratio: argon and oxygen, the ratio of argon and oxygen is 5:9; sputtering pressure is 3 to 5×10 -3 mbar;
[0037] N. Magnetron sputtering 14th layer
[0038] Target quantity: 1 DC plane target; target configuration is silver (Ag); process gas ratio: pure argon; sputtering gas pressure is 2-3×10 -3 mbar;
[0039] O. Magnetron sputtering fifteenth layer
[0040] Target quantity: 1 AC flat target; target configuration is titanium (Ti); process gas ratio: pure argon; sputtering gas pressure is 2-3×10 -3 mbar;
[0041] P, magnetron sputtering sixteenth layer
[0042] Target quantity: 2-3 AC plane targets; target configuration is zinc-aluminum alloy (ZnAl); process gas ratio: argon and oxygen, the ratio of argon and oxygen is 5:9; sputtering pressure is 3-5×10 -3 mbar
[0043] Q. Magnetron sputtering seventeenth layer
[0044] Target quantity: 3-4 AC rotating targets; target configuration is silicon aluminum (SiAl); process gas ratio: argon and nitrogen, argon and oxygen ratio is 7:6; sputtering pressure is 3-5×10 -3 mbar;
[0045] R, magnetron sputtering eighteenth layer
[0046] Target quantity: 1 to 2 AC plane targets; target configuration is zirconium (Zr); process gas ratio: argon and oxygen, the ratio of argon and oxygen is 100:3; sputtering pressure is 3 to 5×10 -3 mbar
[0047] 4) The total film thickness is controlled at 160-349 nm, and the transmission speed of the sputtering chamber is generally controlled at 3.0-6.5 m / min.
[0048] Advantages of the present invention:
[0049] 1. The transmittance of the 6mm ultra-white single-piece product of this patented technology is T∈[50, 60], a*∈[0, -3], b*∈[-1, +3]; the glass surface color is a*∈[-1, -2], b*∈[-6, -10]; the film surface color is a*∈[0, -15], b*∈[0, +5]; the light-to-heat ratio performance is>1.9.
[0050] 2. It can be processed by off-site subsequent cutting, edging, tempering or bending, etc. It can be produced on a large scale and is not easily scratched or oxidized during long-term transportation and storage.
[0051] 3. This coated glass adopts a silicon nitride sandwich structure, which effectively adjusts the reflection effect of the glass and makes its visible light transmission color neutral.
[0052] 4. In this coated glass, a titanium layer is plated on top of the outermost low-emissivity functional layer (silver layer). In the subsequent tempering process, the two layers are combined with each other to form a silver-titanium alloy layer, which further improves the transmittance of the glass.
[0053] 5. In this coated glass, zinc tin oxide is used as the dielectric layer with higher light absorption and transmission performance, thereby making the coated glass more neutral in visible light transmission color. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 It is a schematic diagram of the layered structure of the coated glass.
[0055] In the figure, G, glass substrate layer; 1, first layer; 2, second layer; 3, third layer; 4, fourth layer; 5, fifth layer; 6, sixth layer; 7, seventh layer; 8, eighth layer; 9, ninth layer; 10, tenth layer; 11, eleventh layer; 12, twelfth layer; 13, thirteenth layer; 14, fourteenth layer; 15, fifteenth layer; 16, sixteenth layer; 17, seventeenth layer; 18, eighteenth layer. DETAILED DESCRIPTION
[0056] The present invention will be described in detail below in conjunction with the accompanying drawings.
[0057] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0058] Embodiment 1: The structure of the low-emissivity coated glass of the embodiment of the present invention is as follows.
[0059] like Figure 1 As shown, a tempered medium-low transmittance three-silver low-emissivity coated glass, the coated glass comprises a glass substrate layer G and a coating layer, the coating layer is compounded with eighteen film layers in sequence from the glass substrate layer G to the outside, wherein the first layer 1 is a silicon nitride layer, the second layer 2 is a nickel-chromium nitride layer, the third layer 3 is a silicon nitride layer, the fourth layer 4 is a zinc-aluminum oxide layer, the fifth layer 5 is a silver layer, the sixth layer 6 is a nickel-chromium alloy layer, the seventh layer 7 is a zinc-aluminum oxide layer, the eighth layer 8 is a zinc-tin oxide layer, the ninth layer 9 is a zinc-aluminum oxide layer, the tenth layer 10 is a silver layer, the eleventh layer 11 is a nickel-chromium alloy layer, the twelfth layer 12 is a zinc-tin oxide layer, the thirteenth layer 13 is a zinc-aluminum oxide layer, the fourteenth layer 14 is a silver layer, the fifteenth layer 15 is a titanium layer, the sixteenth layer 16 is a zinc-aluminum oxide layer, the seventeenth layer 17 is a silicon nitride layer, and the eighteenth layer 18 is a zirconium oxide layer.
[0060] In this coated glass, we add a nickel-chromium nitride layer to its coating layer, and nickel-chromium nitride has good light absorption, thereby improving the sunshade effect of the entire coated glass. The nickel-chromium nitride layer is set at the bottom of the entire film layer (before the low-emissivity functional layer) so that the entire film layer can absorb light in advance, thereby reducing the reflection of the coated glass and reducing light pollution. More importantly, considering that the thickness of the underlying coating layer (silicon nitride layer) has a great influence on the appearance color of the glass, especially it can play a decisive role in the color change before and after the glass is tempered, we set the nickel-chromium nitride layer between two thinner silicon nitride layers without changing the thickness of the underlying coating layer, forming a sandwich structure of silicon nitride layer + nickel-chromium nitride layer + silicon nitride layer at the bottom of the coating layer. At the same time, this sandwich structure makes it easier for us to adjust the transmittance color of the coated glass.
[0061] Embodiment 2: The structure of the low-emissivity coated glass in the embodiment of the present invention is as follows.
[0062] like Figure 1 As shown, the coating thickness of the first layer 1 is 10-40 nanometers, the coating thickness of the second layer 2 is 2-10 nanometers, the coating thickness of the third layer 3 is 5-10 nanometers, the coating thickness of the fourth layer 4 is 5-10 nanometers, the coating thickness of the fifth layer 5 is 10-15 nanometers; the coating thickness of the sixth layer 6 is 1-3 nanometers; the coating thickness of the seventh layer 7 is 10-15 nanometers; the coating thickness of the eighth layer 8 is 15-30 nanometers; the coating thickness of the ninth layer 9 is 10-20 nanometers; the coating thickness of the tenth layer 10 is 10-20 nanometers. The coating thickness is 10 to 20 nanometers; the coating thickness of the eleventh layer 11 is 1 to 3 nanometers; the coating thickness of the twelfth layer 12 is 30 to 80 nanometers; the coating thickness of the thirteenth layer 13 is 5 to 20 nanometers; the coating thickness of the fourteenth layer 14 is 10 to 20 nanometers; the coating thickness of the fifteenth layer 15 is 1 to 3 nanometers; the coating thickness of the sixteenth layer 16 is 5 to 10 nanometers; the coating thickness of the seventeenth layer 17 is 15 to 30 nanometers; the coating thickness of the eighteenth layer 18 is 5 to 10 nanometers.
[0063] Embodiment 3: The method for preparing the low-emissivity coated glass comprises the following steps:
[0064] 1) Selecting float glass as the glass substrate layer G;
[0065] 2) Use a coating-specific washing machine to clean and dry the glass substrate layer G. Before coating, the surface of the glass substrate layer G must be dry, free of impurities and static electricity; use deionized water for cleaning, and the water resistance must be greater than 10μs / cm;
[0066] 3) Magnetron sputtering coating
[0067] A. Magnetron sputtering first layer 1
[0068] Target quantity: 1 to 2 AC rotating targets; target configuration is silicon aluminum (SiAl); process gas ratio: argon and nitrogen, the ratio of argon and nitrogen is 7:6; sputtering pressure is 3 to 5×10 -3 mbar;
[0069] B. Magnetron sputtering second layer 2
[0070] Target quantity: 1 AC rotating target; target configuration is nickel-chromium alloy (NiCr); process gas ratio: argon and nitrogen, argon and oxygen ratio is 6:1; sputtering gas pressure is 3~5×10 -3 mbar;
[0071] C. Magnetron sputtering third layer 3
[0072] Target quantity: 1 to 2 AC rotating targets; target configuration is silicon aluminum (SiAl); process gas ratio: argon and nitrogen, argon and oxygen ratio is 7:6; sputtering pressure is 3 to 5×10 -3 mbar;
[0073] D. Magnetron sputtering fourth layer 4
[0074] Target quantity: 2 to 4 DC planar targets; target configuration is zinc-aluminum alloy (ZnAl); process gas ratio: argon and oxygen; sputtering gas pressure is 2 to 3×10 -3 mbar;
[0075] E. Magnetron sputtering fifth layer 5
[0076] Target quantity: 1 DC plane target; target configuration is silver (Ag); process gas ratio: pure argon; sputtering gas pressure is 2-3×10 -3 mbar;
[0077] F. Magnetron sputtering sixth layer 6
[0078] Target quantity: 1 AC rotating target; target configuration is nickel-chromium alloy (NiCr); process gas ratio: pure argon; sputtering gas pressure is 2-3×10 -3 mbar;
[0079] G. Magnetron sputtering seventh layer 7
[0080] Target quantity: 1 to 2 AC rotating targets; target configuration is zinc-aluminum alloy (ZnAl); process gas ratio: argon and oxygen, the ratio of argon and oxygen is 5:9; sputtering gas pressure is 3 to 5×10 -3 mbar;
[0081] H. Magnetron sputtering eighth layer 8
[0082] Target quantity: 2 to 4 AC rotating targets; target configuration is zinc-tin alloy (ZnSn); process gas ratio: argon and oxygen, the ratio of argon and oxygen is 5:9; sputtering gas pressure is 3 to 5×10 -3 mbar;
[0083] I. Magnetron sputtering ninth layer 9
[0084] Target quantity: 1 to 2 AC rotating targets; target configuration is zinc-aluminum alloy (ZnAl); process gas ratio: argon and oxygen, the ratio of argon and oxygen is 5:9; sputtering gas pressure is 3 to 5×10-3mbar;
[0085] J. Magnetron sputtering tenth layer 10
[0086] Target quantity: 1 DC plane target; target configuration is silver (Ag); process gas ratio: pure argon; sputtering gas pressure is 2-3×10 -3 mbar;
[0087] K. Magnetron sputtering eleventh layer 11
[0088] Target quantity: 1 AC rotating target; target configuration is nickel-chromium alloy (NiCr); process gas ratio: pure argon; sputtering gas pressure is 2-3×10 -3 mbar;
[0089] L. Magnetron sputtering twelfth layer 12
[0090] Target quantity: 2 to 5 AC rotating targets; target configuration is zinc-tin alloy (ZnSn); process gas ratio: argon and oxygen, the ratio of argon and oxygen is 5:9; sputtering pressure is 3 to 5×10 -3 mbar;
[0091] M, magnetron sputtering thirteenth layer 13
[0092] Target quantity: 2 to 4 AC plane targets; target configuration is zinc-aluminum alloy (ZnAl); process gas ratio: argon and oxygen, the ratio of argon and oxygen is 5:9; sputtering pressure is 3 to 5×10 -3 mbar;
[0093] N, magnetron sputtering fourteenth layer 14
[0094] Target quantity: 1 DC plane target; target configuration is silver (Ag); process gas ratio: pure argon; sputtering gas pressure is 2-3×10 -3 mbar;
[0095] O. Magnetron sputtering fifteenth layer 15
[0096] Target quantity: 1 AC flat target; target configuration is titanium (Ti); process gas ratio: pure argon; sputtering gas pressure is 2-3×10 -3 mbar;
[0097] P, magnetron sputtering sixteenth layer 16
[0098] Target quantity: 2-3 AC plane targets; target configuration is zinc-aluminum alloy (ZnAl); process gas ratio: argon and oxygen, the ratio of argon and oxygen is 5:9; sputtering pressure is 3-5×10 -3 mbar
[0099] Q, magnetron sputtering seventeenth layer 17
[0100] Target quantity: 3-4 AC rotating targets; target configuration is silicon aluminum (SiAl); process gas ratio: argon and nitrogen, argon and oxygen ratio is 7:6; sputtering pressure is 3-5×10 -3 mbar;
[0101] R, magnetron sputtering eighteenth layer 18
[0102] Target quantity: 1 to 2 AC plane targets; target configuration is zirconium (Zr); process gas ratio: argon and oxygen, the ratio of argon and oxygen is 100:3; sputtering pressure is 3 to 5×10 -3 mbar
[0103] 4) The total film thickness is controlled at 160-349 nm, and the transmission speed of the sputtering chamber is generally controlled at 3.0-6.5 m / min.
[0104]
[0105]
[0106] After testing, the color parameters of the coated glass of this embodiment before and after tempering are shown in Table 2 below:
[0107]
[0108] After testing, the performance parameters of the coated glass after tempering in this embodiment are shown in Table 3 below:
[0109]
[0110] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner without departing from the spirit of the present invention or exceeding the scope defined by the appended claims.
Claims
1. A temperable medium-low transmittance triple-silver low-emissivity coated glass, characterized in that: The coated glass comprises a glass substrate layer (G) and a coating layer, wherein the coating layer is compounded with eighteen film layers in sequence from the glass substrate layer (G) outwards, wherein the first layer (1) is a silicon nitride layer, the second layer (2) is a nickel-chromium nitride layer, the third layer (3) is a silicon nitride layer, the fourth layer (4) is a zinc-aluminum oxide layer, the fifth layer (5) is a silver layer, the sixth layer (6) is a nickel-chromium alloy layer, the seventh layer (7) is a zinc-aluminum oxide layer, the eighth layer (8) is a zinc-tin oxide layer, the ninth layer (9) is a zinc-aluminum oxide layer, the tenth layer (10) is a silver layer, the eleventh layer (11) is a nickel-chromium alloy layer, the twelfth layer (12) is a zinc-tin oxide layer, the thirteenth layer (13) is a zinc-aluminum oxide layer, the fourteenth layer (14) is a silver layer, the fifteenth layer (15) is a titanium layer, the sixteenth layer (16) is a zinc-aluminum oxide layer, the seventeenth layer (17) is a silicon nitride layer, and the eighteenth layer (18) is a zirconium oxide layer.
2. The temperable medium-low transmittance triple-silver low-emissivity coated glass according to claim 1, characterized in that: The coating thickness of the first layer (1) is 10 to 40 nanometers, the coating thickness of the second layer (2) is 2 to 10 nanometers, the coating thickness of the third layer (3) is 5 to 10 nanometers, the coating thickness of the fourth layer (4) is 5 to 10 nanometers, the coating thickness of the fifth layer (5) is 10 to 15 nanometers; the coating thickness of the sixth layer (6) is 1 to 3 nanometers; the coating thickness of the seventh layer (7) is 10 to 15 nanometers; the coating thickness of the eighth layer (8) is 15 to 30 nanometers; the coating thickness of the ninth layer (9) is 10 to 20 nanometers; the coating thickness of the tenth layer (1 The coating thickness of the eleventh layer (11) is 1 to 3 nanometers; the coating thickness of the twelfth layer (12) is 30 to 80 nanometers; the coating thickness of the thirteenth layer (13) is 5 to 20 nanometers; the coating thickness of the fourteenth layer (14) is 10 to 20 nanometers; the coating thickness of the fifteenth layer (15) is 1 to 3 nanometers; the coating thickness of the sixteenth layer (16) is 5 to 10 nanometers; the coating thickness of the seventeenth layer (17) is 15 to 30 nanometers; and the coating thickness of the eighteenth layer (18) is 5 to 10 nanometers.
3. A method for preparing the temperable medium-low transmittance triple-silver low-emissivity coated glass according to claim 1, characterized in that: This method comprises the following steps: 1) Selecting a float glass substrate as the glass substrate layer (G); 2) Use a coating-specific washing machine to clean and dry the glass substrate layer (G). Before coating, the surface of the glass substrate layer (G) must be dry, free of impurities and static electricity; use deionized water for cleaning, and the water resistance must be greater than 10μs / cm; 3) Magnetron sputtering coating A. Magnetron sputtering first layer (1) Target quantity: 1 to 2 AC rotating targets; target configuration is silicon aluminum (SiAl); process gas ratio: argon and nitrogen, the ratio of argon to nitrogen is 7:6; The sputtering pressure is 3~5×10 -3 mbar; B. Magnetron sputtering second layer (2) Target quantity: 1 AC rotating target; target configuration is nickel-chromium alloy (NiCr); process gas ratio: argon and nitrogen, argon and oxygen ratio is 6:1; sputtering gas pressure is 3~5×10 -3 mbar; C. Magnetron sputtering third layer (3) Target quantity: 1 to 2 AC rotating targets; target configuration is silicon aluminum (SiAl); process gas ratio: argon and nitrogen, argon and oxygen ratio is 7:6; sputtering pressure is 3 to 5×10 -3 mbar; D. Magnetron sputtering fourth layer (4) Target quantity: 2 to 4 DC planar targets; target configuration is zinc-aluminum alloy (ZnAl); process gas ratio: argon and oxygen; sputtering gas pressure is 2 to 3×10 -3 mbar; E. Magnetron sputtering fifth layer (5) Target quantity: 1 DC plane target; target configuration is silver (Ag); process gas ratio: pure argon; The sputtering pressure is 2~3×10 -3 mbar; F. Magnetron sputtering sixth layer (6) Target quantity: 1 AC rotating target; target configuration is nickel-chromium alloy (NiCr); process gas ratio: pure argon; The sputtering pressure is 2~3×10 -3 mbar; G. Magnetron sputtering seventh layer (7) Target quantity: 1 to 2 AC rotating targets; target configuration is zinc-aluminum alloy (ZnAl); process gas ratio: argon and oxygen, the ratio of argon and oxygen is 5:9; sputtering gas pressure is 3 to 5×10 -3 mbar; H. Magnetron sputtering eighth layer (8) Target quantity: 2 to 4 AC rotating targets; target configuration is zinc-tin alloy (ZnSn); process gas ratio: argon and oxygen, the ratio of argon to oxygen is 5:9; The sputtering pressure is 3~5×10 -3 mbar; I. Magnetron sputtering ninth layer (9) Target quantity: 1 to 2 AC rotating targets; target configuration is zinc-aluminum alloy (ZnAl); process gas ratio: argon and oxygen, the ratio of argon and oxygen is 5:9; sputtering gas pressure is 3 to 5×10-3mbar; J. Magnetron sputtering tenth layer (10) Target quantity: 1 DC plane target; target configuration is silver (Ag); process gas ratio: pure argon; The sputtering pressure is 2~3×10 -3 mbar; K. Magnetron sputtering eleventh layer (11) Target quantity: 1 AC rotating target; target configuration is nickel-chromium alloy (NiCr); process gas ratio: pure argon; The sputtering pressure is 2~3×10 -3 mbar; L. Magnetron sputtering twelfth layer (12) Target quantity: 2 to 5 AC rotating targets; target configuration is zinc-tin alloy (ZnSn); process gas ratio: argon and oxygen, the ratio of argon and oxygen is 5:9; sputtering gas pressure is 3 to 5×10 -3 mbar; M, magnetron sputtering thirteenth layer (13) Target quantity: 2 to 4 AC plane targets; target configuration is zinc-aluminum alloy (ZnAl); process gas ratio: argon and oxygen, the ratio of argon to oxygen is 5:9; The sputtering pressure is 3~5×10 -3 mbar; N. Magnetron sputtering fourteenth layer (14) Target quantity: 1 DC plane target; target configuration is silver (Ag); process gas ratio: pure argon; The sputtering pressure is 2~3×10 -3 mbar; O. Magnetron sputtering fifteenth layer (15) Target quantity: 1 AC flat target; target configuration is titanium (Ti); process gas ratio: pure argon; The sputtering pressure is 2~3×10 -3 mbar; P, magnetron sputtering sixteenth layer (16) Target quantity: 2 to 3 AC plane targets; target configuration is zinc-aluminum alloy (ZnAl); process gas ratio: argon and oxygen, the ratio of argon and oxygen is 5:9; sputtering pressure is 3 to 5×10 -3 mbar Q. Magnetron sputtering seventeenth layer (17) Target quantity: 3-4 AC rotating targets; target configuration is silicon aluminum (SiAl); process gas ratio: argon and nitrogen, argon and oxygen ratio is 7:6; sputtering pressure is 3-5×10 -3 mbar; R, magnetron sputtering eighteenth layer (18) Target quantity: 1 to 2 AC plane targets; target configuration is zirconium (Zr); process gas ratio: argon and oxygen, the ratio of argon to oxygen is 100:3; The sputtering pressure is 3~5×10 -3 mbar 4) The total film thickness is controlled at 160-349 nm, and the transmission speed of the sputtering chamber is controlled at 3.0-6.5 m / min.
Citation Information
Patent Citations
Neutral gray low-emissivity coated glass and preparation method thereof
CN111825339A
Three-silver medium-transmittance high-performance low-radiation energy-saving coated glass and application thereof
CN117088620A
Privacy coated glass and preparation method thereof
CN118619560A
High-performance temperable high-transmittance three-silver low-emissivity coated glass and preparation method thereof
CN118908592A
Low-reflection three-silver coated glass
CN219792835U
Cited By
Low-radiation anti-reflection type coated glass for automobile skylight and preparation method of low-radiation anti-reflection type coated glass
CN121609517A